Evaluating increased effort for item disposal to improve recycling at a university. Issue 4 (13th September 2017) - Fritz, Jennifer N.; Dupuis, Danielle L.; Wu, Wai‐Ling; Neal, Ashley E.; Rettig, Lisa A.; Lastrapes, Renée E.
Abstract : An evaluation of increased response effort to dispose of items was conducted to improve recycling at a university. Signs prompting individuals to recycle and notifying them of the location of trash and recycling receptacles were posted in each phase. During the intervention, trashcans were removed from the classrooms, and one large trashcan was available in the hallway next to the recycling receptacles. Results showed that correct recycling increased, and trash left in classrooms increased initially during the second intervention phase before returning to baseline levels.